Instructional Design of "Images of Quadratic Functions" - Zhou, Xudong (International Journal of Social Sciences and Public Administration, 2024)
Classroom teaching is an indispensable part of education, and it is particularly important for teachers to carry out preset teaching design according to curriculum standards and teaching methods before teaching to determine whether classroom teaching can be carried out smoothly. After the release of the 2022 edition of the Compulsory Education Mathematics Curriculum Standards, this paper is based on the teaching design of the image of quadratic functions in the ninth grade curriculum according to the requirements of the new curriculum standards. It aims to provide new methods and ideas for the teaching process of quadratic function images. Through the analysis of curriculum standards, the objectives of this course are clarified, and the teaching process of this course is designed in combination with the teaching process of similar courses in the compulsory education stage. The resulting teaching design starts from the analysis of teaching materials, combines the students' learning situation and the teaching objectives that need to be achieved, analyzes the key points and difficulties of teaching, and carries out the teaching design of the complete course content according to the reasonable teaching method, and designs the board books in the course of the class and leaves homework after class: the consolidation and further exploration of the quadratic function.